MEDIA AND NATIONAL INTEGRATION: WITH SPECIAL REFERENCE TO DANCE REALITY SHOWS - Dr Indira Bali (IJRDO- Journal of Educational Research, 2017)
This paper explores the evolving dynamics of national integration in India through the lens of media, with a particular focus on dance and music reality shows. Tracing India’s diverse socio-cultural fabric from the time of independence to the present day, the study raises pertinent questions about the formation and endurance of a unified national identity. It argues that despite political, linguistic, and regional divisions, mass media—especially television and digital platforms— have emerged as powerful tools for fostering emotional and cultural unity. Programs such as Kaun Banega Crorepati, India’s Got Talent, Sa Re Ga Ma Pa, Dance India Dance, and Just Dance transcend boundaries of language, religion, and region by promoting shared emotions, aspirations, and participation. The paper highlights how stories of ordinary individuals achieving national recognition inspire a sense of collective pride and belonging among viewers. Furthermore, it emphasizes the dual role of traditional Indian cultural elements and global dance forms in shaping a modern, inclusive, and aspirational identity. Ultimately, the study concludes that media, particularly music